Pengaruh Pertumbuhan Laba Perusahaan Asuransi yang Terdaftar di BEI Periode 2020-2023 terhadap Pendapatan Premi, Pembayaran Klaim, Risk Based Capital, dan Hasil Investasi - Novitasari, Nindy Irja; Zaman, Badrus; Widiati, Hestin Sri (FEB Universitas Maritim Semarang, 2025)
The purpose of this study is to identify the variables that affect profit growth. Profit growth is the study's dependent variable, and premium income, claim payments, risk-based capital, and investment returns are its independent variables. Information was gathered from insurance firms that were listed between 2019 and 2023 on the Indonesia Stock Exchange. Ten businesses that satisfied specific requirements made up the study's sample. To get a complete picture of the link between one variable and another, multiple linear regression analysis was employed as the study approach, with a 5% confidence level. The factors Premium Income, Claim Payments, Risk-Based Capital, and Investment Returns all had a somewhat significant impact on Profit Growth, according to the partial test results. The factors Premium Income, Claim Payments, Risk-Based Capital, and Investment Returns all had a substantial impact on Profit Growth at the same time, according to the results of the simultaneous test. It is anticipated that other businesses listed on the BEI will use the study's findings as a guide to focus more on financial ratios in order to boost their profits.